Perlindungan Hukum Nasabah Kartu Kredit dalam Perspektif Undang-Undang Nomor 8 Tahun 1999 - Nyoman Triananda Prayoga; I Nyoman Sujana; Ni Made Puspasutari Ujianti (Jurnal Preferensi Hukum, 2021)
At this time the technology has been developing rapidly, as well as means of payment. If the first payment can only be done with cash, current payment already can be done by credit card. When the first buyers and sellers have to meet directly, unlike with the current buyers no longer have to meet with the seller directly. A credit card is a plastic card issued by a bank that provides credit services. But many cases credit card used another person, which is possible because the card is missing or scams online, these problems can be analysed as follows: 1) What kind of legal protection for customers according to credit card Consumer Protection Legislation? 2) How the legal consequences if a credit card were used by someone else? This presentation uses research methods are normative, legal rules and legal norms according are the norm in the form of orders or prohibitions it in accordance with the principle of the law and whether one's actions is in compliance with legal norms with the approach of legislative and conceptual. This research requires a source of secondary legal materials as primary legal materials. Form of legal protection given by the Government in the form of legislation, but the legislation has not been effective. Legal consequences if the credit card used another person's credit card, the customer must still pay the Bills that go up to the customer to report in writing. The Government should streamline the laws and make special laws about credit cards as well as the bank and the customer must be open.